CoS / CuCo2S4 photocatalyst as well as preparation method and application thereof
By constructing a hollow spherical heterostructure of CoS/CuCo2S4 with sulfur-rich vacancy and interface Co-S bonding, the problem of loose interface contact of the photocatalyst is solved, and efficient CO2 reduction is achieved, which improves the generation rate and selectivity of C2H4.
Patent Information
- Application Number
- CN202510796428.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-06-16
AI Technical Summary
When existing photocatalysts generate high added value C2+ products such as C2H2, C2H4, and C2H6 in C-C coupling, loose interface contact leads to poor transmission of photogenerated carriers, limiting the CO2 reduction performance.
A one-step hydrothermal method is used to construct a CoS/CuCo2S4 hollow spherical type II heterostructure with sulfur-rich vacancy and interface Co-S bonding. The interface Co-S bonds are used as an atomic channel to promote the separation and transmission of photogenerated carriers, and the active sites are optimized to enhance CO2 reduction activity.
The performance of C2H4 produced by CO2 photoreduction was significantly improved. The yield and electron selectivity of C2H4 reached 28.79 μmol g-1h-1 and 93.95%, respectively, and the product selectivity was 72.14%, which optimized the C-C coupling process and reduced the activation energy barrier.
Smart Images

Figure CN120325299A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of catalysts, and specifically relates to a CoS / CuCo2S4 photocatalyst, its preparation method and application. Background Art
[0002] The photocatalytic CO2 reduction technology driven by solar energy can convert it into high-value chemicals. In the CO2 photoreduction product system, C1 products (such as CH4, especially CO) have become a research hotspot due to their relatively low kinetic energy barriers. However, for the specific needs of the energy field and the industrial community, how to generate high-value C 2+ products (such as C2H2, C2H4, C2H6) through C-C coupling still faces major challenges. As a key raw material in the chemical, biological, and pharmaceutical industries, the synthesis research of ethylene (C2H4) has both scientific exploration and industrial application values.
[0003] Currently, photocatalysts such as ZnSe-CsSnCl3, Mn3O4 / FeNbO4, TiO2 / In2O3, BiOIO3 / Bi-MOF have shown enhanced CO2 reduction activities. However, the interfacial forces of most reported type-II heterojunctions only rely on weak physical adsorption and stacking forces, resulting in loose interfacial contact. This will generate significant charge migration resistance, which is not conducive to the high-throughput transport of photo-generated carriers at the interface between components, thus limiting their CO2 reduction performance. Summary of the Invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a CoS / CuCo2S4 photocatalyst, its preparation method and application. The specific technical solutions are as follows: In the first aspect, the present invention provides a preparation method of a CoS / CuCo2S4 photocatalyst, including the following steps: Dissolve Co(NO3)2·6H2O and Cu(NO3)2·3H2O in ethylene glycol respectively to obtain a first solution and a second solution; then while stirring, drop the second solution into the first solution to obtain a third solution; Continue to stir the third solution, and then add sodium dimethyldithiocarbamate to obtain a suspension; Perform a hydrothermal reaction on the suspension, and after the reaction is completed, centrifuge, wash, and dry to obtain the CoS / CuCo2S4 photocatalyst.
[0005] The present invention successfully constructs sulfur vacancy-rich (V S), CoS / CuCo2S4 (CS / CCS) hollow spherical type-II heterostructure with interfacial Co-S bonding. During the above preparation process, the ternary copper cobalt sulfide (CuCo2S4) has a cubic spinel structure (space group Fd-3m), and Cu and Co atoms occupy tetrahedral and octahedral sites respectively. In addition, CoS (CS) has unique advantages. Its conduction band and valence band potentials are respectively lower than those of CCS, and its work function is higher than that of CCS. Moreover, the coupling of CS and CCS can not only form a chemically bonded heterojunction by sharing S atoms at the heterointerface (enhancing interfacial compatibility), but also generate abundant V in the heterojunction based on the atomic sharing mechanism. S .
[0006] As a further preferred embodiment, the molar percentage of Cu(NO3)2·3H2O and Co(NO3)2·6H2O is 1-3:20. It can be seen from the examples and comparative examples of the present invention that when the dosage of Cu(NO3)2·3H2O is too large, only CuCo2S4 nanosheets can be obtained, and the CoS / CuCo2S4 catalyst cannot be obtained.
[0007] As a further preferred embodiment, the molar ratio of Co(NO3)2·6H2O to sodium dimethyldithiocarbamate is 1:2.5-3.
[0008] As a further preferred embodiment, the dropping speed is 1 drop / 6 s - 1 drop / 8 s.
[0009] As a further preferred embodiment, the time for continuously stirring the third solution is 0.3 h - 1 h.
[0010] As a further preferred embodiment, the temperature of the hydrothermal reaction is 160 °C.
[0011] As a further preferred embodiment, the time of the hydrothermal reaction is 16 h.
[0012] In the second aspect, the present invention provides a CoS / CuCo2S4 photocatalyst, which is prepared by the above preparation method.
[0013] In the third aspect, the present invention provides the application of the above CoS / CuCo2S4 photocatalyst in photocatalytic CO2 reduction.
[0014] As a further preferred embodiment, the above CoS / CuCo2S4 photocatalyst is used for photocatalytic CO2 to C2H4.
[0015] The beneficial effects of the present invention are as follows: The present invention provides a V-rich S, Preparation method of CoS / CuCo2S4 hollow spherical type-II heterostructure photocatalyst with interfacial Co-S bond connection. The synthesis method has mild reaction conditions and is easy to operate. Among them, the interfacial Co-S bond effectively promotes the separation and transport of photo-generated carriers as an atomic-level channel, enabling a large amount of photo-generated electrons to be enriched on the CCS surface and stably exist at the active sites, thereby enhancing the CO2 photoreduction activity. V S The introduction of V induces a highly delocalized electron distribution and shortens the adjacent Cu-Co atomic spacing, resulting in the local metallization of Cu and Co atoms and the formation of Cu-Co dual sites connected by metal bonds. These sites not only transform the endothermic rate-determining step (*CO dimerization to *COCO) of a single CCS into an exothermic process (promoting C-C coupling), but also reduce the overall activation energy barrier, synergistically promoting the formation of C2H4. Finally, the optimized photocatalyst uses H2O vapor as the hydrogen source and hole scavenger, and exhibits excellent performance in photocatalytic CO2 reduction to C2H4: the C2H4 yield and electron selectivity reach 28.79 μmol g -1 h -1 and 93.95%, and the product selectivity is 72.14%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0017] Figure 1 Shown are transmission electron microscope (TEM) images and high-resolution transmission electron microscope (HRTEM) images. Among them, (a) and (b) in the figure are TEM images of CS HNs; (c) in the figure is the high-resolution transmission electron microscope (HRTEM) image of CS HNs; (d) and (e) in the figure are TEM images of CCS NSs; (f) in the figure is the high-resolution transmission electron microscope (HRTEM) image of CCS NSs; (g) in the figure is the HRTEM image of CS / CCS-10; (h) in the figure is the HRTEM image of CS / CCS-10; (i) in the figure is the elemental distribution map of CS / CCS-10; (j) in the figure is the Cu elemental distribution map; (k) in the figure is the Co elemental distribution map; (l) in the figure is the S elemental distribution map.
[0018] Figure 2Shown are the electron paramagnetic resonance (EPR) spectra, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) spectra, and Raman spectra; among them, (a) in the figures is the EPR diagram of CS / CCS-10 and CS HNs; (b) in the figures is the XRD diagram of CS / CCS-5, CS / CCS-10, CS / CCS-15, CS HNs, and CCS NSs; (c) in the figures is the FTIR diagram of CS / CCS-10, CS HNs, and CCS NSs; (d) in the figures is the Raman spectrum of CS / CCS-10, CS HNs, and CCS NSs. Figure 3 Shown are the photocatalytic CO2 reduction performance test diagrams; among them, (a) and (b) in the figures are the photocatalytic CO2 reduction performance test diagrams of CS / CCS-5, CS / CCS-10, CS / CCS-15, CS HNs, and CCS NSs, (c) in the figures is the photocatalytic CO2 reduction cycle test diagram of CS / CCS-10; (d) in the figures is the photocatalytic 13 CO2 generation 13 C2H4 and 13 the mass spectrometry diagram of CO.
[0019] Figure 4 Shown are the energy band diagrams before and after the catalyst contact and the schematic diagram of the photocatalytic CO2 reduction mechanism provided by the comparative example; among them, (a) and (b) in the figures are the energy band diagrams of CCS NSs and CS HNs before and after contact, respectively; (c) in the figures is the schematic diagram of the photocatalytic CO2 reduction mechanism of the heterostructure constructed by CCSNSs and CS HNs.
[0020] Figure 5 Shown are the surface potential images before and after illumination; among them, (a) and (b) in the figures are the surface potential images of CSHNs in the dark and after illumination, respectively; (d) and (e) in the figures are the surface potential images of CS / CCS-10 in the dark and after illumination, respectively; (c) and (f) in the figures are the line-scan surface potential differences of CS HNs and CS / CCS-10, where ΔCPD = CPD 光照 - CPD 暗处 .
[0021] Figure 6The ultraviolet-visible absorption spectrum, transient photocurrent response spectrum, electrochemical impedance spectrum, and photoluminescence spectrum are shown; among them, (a) in the figure is the ultraviolet-visible absorption spectrum of CS / CCS-5, CS / CCS-10, CS / CCS-15, CS HNs, and CCS NSs; (b) in the figure is the transient photocurrent response spectrum of CS / CCS-10, CS HNs, CCS NSs, and CS / CCS-M; (c) in the figure is the electrochemical impedance spectrum of CS / CCS-10, CS HNs, CCS NSs, and CS / CCS-M; (d) in the figure is the photoluminescence spectrum of CS / CCS-10, CS HNs, and CCS NSs.
[0022] Figure 7 The CO2 temperature-programmed desorption curve, in-situ FTIR diagram of CO2 photoreduction, adsorption energy of CO on different active sites, Bader charges of surface cobalt and copper sites without Vs and with Vs, and electron localization function diagrams without Vs and with Vs are shown; among them, (a) in the figure is the CO2 temperature-programmed desorption curve of CS / CCS-10, CCS NSs, and CS HNs; (b) in the figure is the in-situ FTIR diagram of CO2 photoreduction on CS / CCS-10; (c) and (d) in the figure are the adsorption energies of CO on different active sites of CCS NSs and CS / CCS-10, respectively; (e) and (f) in the figure are the Bader charges of surface cobalt and copper sites of CS / CCS-10 without Vs and with Vs, respectively; (g) and (h) in the figure are the electron localization function diagrams of CS / CCS-10 without Vs and with Vs, respectively. Detailed implementation manners
[0023] Next, the technical solutions in the embodiments of the present application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without making creative efforts belong to the scope protected by the present application.
[0024] Example 1 A preparation method of a sulfur-rich vacancy and interface Co-S bond-connected CoS / CuCo2S4 hollow spherical type-II heterostructure photocatalyst specifically includes the following steps: (1) Dissolve 0.6 mmol of Co(NO3)2·6H2O in 20 mL of ethylene glycol (EG) to form solution A; (2) Dissolve 0.03 mmol of Cu(NO3)2·3H2O in 20 mL of EG to prepare solution B; (3) Add solution B dropwise (1 drop per 7 seconds) to solution A under vigorous stirring to obtain solution C; (4) After continuing to stir for 0.5 h, add 1.5 mmol of sodium dimethyldithiocarbamate to solution C to obtain suspension D; (5) Transfer suspension D to a 100 mL hydrothermal autoclave, carry out hydrothermal reaction at 160 °C for 16 h to obtain a black precipitate, centrifuge at 10000 rpm for 5 min, wash 3 times with deionized water, and finally dry in a freeze dryer for 12 hours; obtain a sulfur-rich vacancy and interface Co-S bond-connected CoS / CuCo2S4 hollow spherical type II heterostructure photocatalyst.
[0025] In the CoS / CuCo2S4 heterostructure photocatalyst of this example, the molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O used is 1:20, and this CoS / CuCo2S4 heterostructure photocatalyst is labeled as CS / CCS-5.
[0026] Example 2 A preparation method of a sulfur-rich vacancy and interface Co-S bond-connected CoS / CuCo2S4 hollow spherical type II heterostructure photocatalyst specifically includes the following steps: (1) Dissolve 0.6 mmol of Co(NO3)2·6H2O in 20 mL of ethylene glycol (EG) to form solution A; (2) Dissolve 0.06 mmol of Cu(NO3)2·3H2O in 20 mL of EG to prepare solution B; (3) Add solution B dropwise (1 drop per 7 seconds) to solution A under vigorous stirring to obtain solution C; (4) After continuing to stir for 0.5 h, add 1.5 mmol of sodium dimethyldithiocarbamate to solution C to obtain suspension D; (5) Transfer suspension D to a 100 mL hydrothermal autoclave, carry out hydrothermal reaction at 160 °C for 16 h to obtain a black precipitate, centrifuge at 10000 rpm for 5 min, wash 3 times with deionized water, and finally dry in a freeze dryer for 12 hours; obtain a sulfur-rich vacancy and interface Co-S bond-connected CoS / CuCo2S4 hollow spherical heterostructure photocatalyst.
[0027] In the CoS / CuCo2S4 heterostructure photocatalyst of this example, the molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O used is 2:20, and this CoS / CuCo2S4 heterostructure photocatalyst is labeled as CS / CCS-10.
[0028] Example 3 A preparation method of a CoS / CuCo2S4 hollow spherical type-II heterostructure photocatalyst with rich sulfur vacancies and interfacial Co-S bonds, specifically comprising the following steps: (1) Dissolve 0.6 mmol of Co(NO3)2·6H2O in 20 mL of ethylene glycol (EG) to form solution A; (2) Dissolve 0.09 mmol of Cu(NO3)2·3H2O in 20 mL of EG to prepare solution B; (3) Dropwise add solution B to solution A (1 drop every 7 seconds) under vigorous stirring to obtain solution C; (4) After continuing to stir for 0.5 h, add 1.5 mmol of sodium dimethyldithiocarbamate to solution C to obtain suspension D; (5) Transfer suspension D to a 100 mL hydrothermal autoclave, perform hydrothermal reaction at 160 °C for 16 h to obtain a black precipitate, centrifuge at 10000 rpm for 5 min, wash 3 times with deionized water, and finally dry in a freeze dryer for 12 hours; obtain a CoS / CuCo2S4 hollow spherical heterostructure photocatalyst with rich sulfur vacancies and interfacial Co-S bonds.
[0029] In the CoS / CuCo2S4 heterostructure photocatalyst of this example, the molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O used is 3:20, and this CoS / CuCo2S4 heterostructure photocatalyst is labeled as CS / CCS-15.
[0030] Comparative Example 1 A preparation method of a CoS hollow spherical structure photocatalyst, specifically comprising the following steps: (1) Dissolve 0.6 mmol of Co(NO3)2·6H2O in 20 mL of ethylene glycol (EG) to form solution A.
[0031] (2) After continuing to stir for 0.5 h, add 1.5 mmol of sodium dimethyldithiocarbamate to solution A to obtain suspension B; (3) Transfer suspension B to a 100 mL hydrothermal autoclave, perform hydrothermal reaction at 160 °C for 16 h to obtain a black precipitate, centrifuge at 10000 rpm for 5 min, wash 3 times with deionized water, and finally dry in a freeze dryer for 12 hours; obtain a CoS hollow spherical structure photocatalyst (labeled as CS HNs).
[0032] Comparative Example 2 A preparation method of a CuCo2S4 nanosheet photocatalyst, specifically comprising the following steps: (1) Dissolve 0.6 mmol of Co(NO3)2·6H2O in 20 mL of ethylene glycol (EG) to form Solution A; (2) Dissolve 0.3 mmol of Cu(NO3)2·3H2O in 20 mL of EG to prepare Solution B; (3) Add Solution B dropwise (1 drop / 7 s) to Solution A under vigorous stirring to obtain Solution C; (4) After continuous stirring for 0.5 h, add 1.5 mmol of sodium dimethyldithiocarbamate to Solution C to obtain suspension D; (5) Transfer suspension D to a 100 mL hydrothermal reactor, carry out hydrothermal reaction at 160 °C for 16 h to obtain a black precipitate, centrifuge at a high speed of 10000 rpm for 5 min, wash 3 times with deionized water, and finally dry in a freeze dryer for 12 hours; obtain the CuCo2S4 nanosheet structure photocatalyst.
[0033] In the CuCo2S4 nanosheet photocatalyst of this comparative example, the molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O used is 10:20, and this CuCo2S4 nanosheet photocatalyst is labeled as CCS NSs.
[0034] Comparative Example 3 A preparation method of a physical mixture photocatalyst of CoS hollow spherical structure and CuCo2S4 nanosheets, which specifically includes the following steps: Transfer 0.6 mmol of CS HNs (Comparative Example 1) and 0.06 mmol of CCS NSs (Comparative Example 2) to an agate mortar, grind strongly for 30 min, and obtain a uniformly mixed black powder, labeled as CS / CCS-M.
[0035] Example 4 Analyze the samples of the above Examples 1 - 3 and Comparative Examples 1 - 3 by TEM, XRD, EPR, FTIR, ultraviolet-visible absorption spectroscopy, photoelectrochemical test, CO2 temperature-programmed desorption curve, and in-situ diffuse reflectance Fourier transform infrared spectroscopy of CO2 photoreduction.
[0036] The results are as Figure 1 - Figure 2 and Figure 4 - Figure 7 shown, among which, Figure 1 (a) in Figure 1 (b) in Figure 1 is the TEM image of Comparative Example 1 (CS HNs) of the present invention, Figure 1 (c) inFigure 1 Among them, (e) is the TEM image of Comparative Example 2 (CCS NSs) of the present invention, Figure 1 and (f) is the HRTEM image of Comparative Example 2 (CCS NSs) of the present invention, indicating that CCS NSs have a nanosheet structure. Figure 1 Among them, (g) is the TEM image of Example 2 (CS / CCS-10) of the present invention, Figure 1 and (h) is the HRTEM image of Example 2 (CS / CCS-10) of the present invention, indicating that CS / CCS-10 inherits the hollow spherical structure of CS HNs. Figure 1 Among them, (i) is the elemental distribution map of Example 2 (CS / CCS-10) of the present invention, indicating that the catalyst (CS / CCS-10) prepared in Example 2 is composed of three elements: Cu, Co, and S.
[0037] Figure 2 Among them, (a) is the electron paramagnetic resonance (EPR) spectra of Example 2 (CS / CCS-10) and Comparative Example 1 (CS HNs) of the present invention, indicating that there is almost no Vs in CS HNs, while there are abundant Vs in CS / CCS-10. Figure 2 Among them, (b) is the XRD patterns of Examples 1 - 3 (CS / CCS-5, CS / CCS-10, CS / CCS-15) and Comparative Examples 1 - 2 (CS HNs, CCS NSs) of the present invention, indicating that: the main characteristic diffraction peaks of CS HNs appear at 30.61°, 35.32°, 46.97°, and 54.41°, corresponding to the (100), (101), (102), and (110) planes of hexagonal phase CS (JCPDS no. 65-8977). The main characteristic diffraction peaks of CCS NSs appear at 26.59°, 31.27°, 37.94°, 46.99°, 49.99°, and 54.79°, corresponding to the (022), (113), (004), (224), (115), and (044) planes of cubic phase CCS (JCPDS no.42-1450); It is worth noting that the diffraction peaks of CS / CCS-5, CS / CCS-10, and CS / CCS-15 can all find the characteristic diffraction peaks of CS and CCS, and there are no other impurity characteristic peaks, proving that CS / CCS-5, CS / CCS-10, and CS / CCS-15 are all composed of CS and CCS. Figure 2 Among them, (c) is the Fourier transform infrared spectroscopy (FTIR) patterns of Example 2 (CS / CCS-10) and Comparative Examples 1 - 2 (CS HNs, CCS NSs) of the present invention, Figure 2In (d) is the Raman spectrum of Example 2 (CS / CCS-10) of the present invention, Comparative Example 1 - Comparative Example 2 (CS HNs, CCS NSs), demonstrating the presence of interfacial Co-S bonds in CS / CCS-10.
[0038] Figure 4 In (a) of Figure 4 In (b) of are the energy band diagrams before and after contact between Comparative Example 2 (CCS NSs) and Comparative Example 1 (CS HNs), respectively; Figure 4 In (c) is a schematic diagram of the mechanism of photocatalytic CO2 reduction of CS / CCS-10, indicating that after coupling CCS NSs and CS HNs, a type-II heterostructure is constructed, and under light illumination conditions, it is beneficial for photo-generated electrons and holes to move to CCS NSs and CS HNs respectively, thus being beneficial for the photocatalytic CO2 reduction performance.
[0039] Figure 5 In (a) of Figure 5 In (b) of are the surface potential images of Comparative Example (CS HNs) before and after light illumination, indicating that under dark conditions, the surface potential (SP) of CS HNs is 198.3 mV to -30.0 mV, and under visible light illumination, its SP is 276.5 mV to 90.7 mV; Figure 5 In (d) of Figure 5 In (e) of are the surface potential images of the Example (CS / CCS-10) before and after light illumination, indicating that for CS / CCS-10, the SP value under light illumination (101.7 mV to -191.4 mV) is lower than the SP value under dark conditions (111.3 mV to -154.8 mV), indicating that under light illumination conditions, the photo-generated electrons of CS transfer to CCS; Figure 5 In (c) of Figure 5 In (f) of are the line-scanned surface potential differences (ΔCPD) of the Comparative Example (CS HNs) and the Example (CS / CCS-10), where ΔCPD = CPD 光照 - CPD 暗处 , indicating that the surface potential difference of CS / CCS-10 is 48.7 mV, significantly higher than the surface potential difference of CS HNs (28.7 mV). This confirms the enhanced separation kinetics of photo-generated carriers, promoting the aggregation of photo-generated electrons on the surface of CCS, thus creating a multi-rich electron environment, which is crucial for the reduction of carbon dioxide to C2 products.
[0040] Figure 6Among them, (a) is the UV-visible absorption spectra of Examples 1 - 3 (CS / CCS-5, CS / CCS-10, CS / CCS-15) and Comparative Examples 1 - 2 (CS HNs, CCS NSs) of the present invention. Figure 6 Among them, (b) is the transient photocurrent response spectra of Example 2 (CS / CCS-10) and Comparative Examples 1 - 3 (CS HNs, CCS NSs, CS / CCS-M) of the present invention. Figure 6 Among them, (c) is the electrochemical impedance spectra of Example 2 (CS / CCS-10) and Comparative Examples 1 - 3 (CS HNs, CCS NSs, CS / CCS-M) of the present invention. Figure 6 Among them, (d) is the photoluminescence spectra of Example 2 (CS / CCS-10) and Comparative Examples 1 - 2 (CS HNs, CCS NSs), all of which prove that CS / CCS-10 is beneficial to the separation and transfer of photo-generated charges.
[0041] Figure 7 Among them, (a) is the temperature-programmed desorption curve of CO2 for Example 2 CS / CCS-10 and Comparative Examples 1 - 2 (CCS NSs, CS HNs) of the present invention, indicating that CCS NSs has two desorption peaks (200℃ - 350℃ and 350℃ - 500℃), while CS HNs has only one desorption peak (200℃ - 350℃). In contrast, the peak area of CS / CCS-10 increases significantly at 200℃ - 350℃, and a new peak appears at 500℃ - 600℃, indicating an enhanced CO2 adsorption capacity. Figure 7 Among them, (b) is the in-situ FTIR diagram of CO2 photoreduction on Example 2 (CS / CCS-10) of the present invention, indicating that the characteristic peaks at 1261 cm -1 , 1558 cm -1 , 1580 cm -1 belong to *COOH, and the characteristic peak at 1072 cm -1 belongs to *CHO, proving that CO2 adsorption and activation do occur on the surface of the photocatalyst, and it is a continuous process of proton-coupled electron. The characteristic peak at 1750 cm -1 belongs to CO chemisorption (*CO). Due to the presence of Vs, the Cu-Co bond distance is shortened, and *COCO can be coupled to form. The characteristic peak at 1716 cm -1 belongs to the vibration of the *COCO intermediate. The peak at 1342 cm -1 belongs to *CH2, and the peak at 1445 cm -1 belongs to the vibration of C = C, indicating that CS / CCS-10 does facilitate the formation of C2H4 by shortening the Co-Cu bond distance. At 1680 cm-1 The *CH2=CH2 intermediate that was finally desorbed from the surface was detected at [location], indicating that C2H4 was instantaneously formed during the photocatalytic CO2 reduction process. Figure 7 In (c) of Figure 7 In (d) of Figure 7 In (e) of Figure 7 In (f) of Figure 7 In (g) of Figure 7 In (h) of
[0042] Example 5 Using the five products CS / CCS-5, CS / CCS-10, CS / CCS-15, CCS NSs, and CS HNs obtained from Examples 1 - 3 and Comparative Examples 1 - 2 as photocatalysts for CO2 reduction, the specific steps are as follows: Respectively place 50 mg of the photocatalyst in a sealed glass reactor with an area of 4.2 cm 2A 250 W xenon lamp was used as the light source for the photocatalytic reaction. Before irradiation, the reactor was evacuated using a vacuum pump, and then high-purity CO2 gas was introduced into the reaction device to reach ambient pressure; 0.4 mL of deionized water was injected into the reactor, and the prepared photocatalyst was equilibrated in a CO2 atmosphere for several hours. Through circulating cooling water, the temperature of the reaction system was always maintained at 25 °C; during irradiation, 0.5 mL of gas was extracted from the reaction flask every hour and subjected to subsequent analysis using a gas chromatograph (GC9790 IIA, Fuli Analytical Instruments Co., Ltd., Zhejiang, China), which was equipped with FID and TCD detectors.
[0043] The results are as Figure 3 shown, where Figure 3 in (a) and Figure 3 in (b) are the photocatalytic CO2 reduction performance test diagrams of Examples 1 - 3 (CS / CCS-5, CS / CCS-10, CS / CCS-15) and Comparative Examples 1 - 2 (CS HNs, CCS NSs) of the present invention. The results show that Example CS / CCS-10 has the optimal photocatalytic CO2 reduction performance for C2H4 production (the C2H4 production rate and electron selectivity are 28.79 μmol -1 h -1 and 93.95% respectively, and the product selectivity is 72.14%), which is significantly higher than that of the comparative examples (CS HNs, CCS NSs); the electron selectivity was calculated according to the following formula: (C2H4)=12n(C2H4) / [12n(C2H4)+ 2n(CO)]×100%. The ethylene product selectivity was calculated according to the following formula: (C2H4)=n(C2H4) / [n(C2H4)+ n(CO)]×100%. Wherein, n(C2H4) and n(CO) represent the amounts of substances of C2H4 and CO produced respectively.
[0044] Figure 3 in (c) is the photocatalytic CO2 reduction cycle test diagram of Example 2 (CS / CCS-10) of the present invention, indicating that Example CS / CCS-10 has excellent cycle stability. Figure 3 in (d) is the photocatalytic 13 CO2 generation 13 of C2H4 and 13 CO mass spectrometry diagram of Example 2 (CS / CCS-10) of the present invention, which confirmed the occurrence of the photocatalytic CO2 reduction reaction.
[0045] The embodiments of the present application have been described above in conjunction with the accompanying drawings. Specific examples are used herein to elaborate on the principles and implementation manners of the present application. The description of the above embodiments is only used to help understand the core idea of the present application. However, the present application is not limited to the above specific implementation manners. The above specific implementation manners are merely illustrative rather than restrictive. Those of ordinary skill in the art, under the inspiration of the present application, without departing from the spirit of the present application and the scope protected by the claims, can also make many forms, all of which fall within the protection scope of the present application.
Claims
1. A preparation method of a CoS / CuCo2S4 photocatalyst, characterized in that, It includes the following steps: Dissolve Co(NO3)2·6H2O and Cu(NO3)2·3H2O in ethylene glycol respectively to obtain a first solution and a second solution; then while stirring, drop the second solution into the first solution to obtain a third solution; Continue to stir the third solution, and then add sodium dimethyldithiocarbamate to obtain a suspension; Carry out a hydrothermal reaction on the suspension, and after the reaction is completed, centrifuge, wash, and dry to obtain the CoS / CuCo2S4 photocatalyst.
2. The preparation method according to claim 1, characterized in that, The molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O is 1-3:
20.
3. The preparation method according to claim 2, wherein, The molar ratio of Co(NO3)2·6H2O to sodium dimethyldithiocarbamate is 1:2.5-3.
4. The preparation method according to claim 1, characterized in that, The dropping speed is 1 drop / 6 s - 1 drop / 8 s.
5. The preparation method according to claim 1, wherein The stirring time of the third solution is 0.3 h - 1 h.
6. The preparation method according to claim 1, characterized in that, The temperature of the hydrothermal reaction is 160 °C.
7. The preparation method according to claim 6, characterized in that The time of the hydrothermal reaction is 16 h.
8. A CoS / CuCo2S4 photocatalyst, characterized in that, Prepared by the preparation method according to any one of claims 1-7.
9. Application of the CoS / CuCo2S4 photocatalyst according to claim 8 in photocatalytic CO2 reduction.
10. The application according to claim 9, wherein The CoS / CuCo2S4 photocatalyst is used for photocatalytic CO2 to produce C2H4.
Citation Information
Patent Citations
Preparation method of cadmium sulfide-molybdenum sulfide-tungsten sulfide heterojunction photocatalytic composite material with urchin-like structure and application of cadmium sulfide-molybdenum sulfide-tungsten sulfide heterojunction photocatalytic composite material
CN107670676A
Preparation method and application of flaky copper-cobalt bimetallic sulfide catalytic material
CN111841577A
CuSCN / CoS2 composite photocatalytic material, preparation method and application
CN115709090A
2D / 3D nano flower-shaped CuCo2S4-coated Co3O4 catalyst as well as preparation method and application of 2D / 3D nano flower-shaped CuCo2S4-coated Co3O4 catalyst
CN118807783A
Method for producing oxidized titanium particle
JP2010088964A